2017
DOI: 10.1111/1365-2664.12894
|View full text |Cite
|
Sign up to set email alerts
|

Soil drainage facilitates earthworm invasion and subsequent carbon loss from peatland soil

Abstract: Summary 1. Human activities have been a significant driver of environmental changes with tremendous consequences for carbon dynamics. Peatlands are critical ecosystems because they store ~30% of the global soil organic carbon pool and are particularly vulnerable to anthropogenic changes. The Zoige peatland on the eastern Tibet Plateau, as the largest alpine peatland in the world, accounts for 1‰ of global peat soil organic carbon storage. However, this peatland has experienced dramatic climate change including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 41 publications
(101 reference statements)
0
9
0
1
Order By: Relevance
“…See aerobic and anaerobic decomposition in Figure 1. Drawdown alleviates oxygen limitation and increases soil aeration, which promotes the activities of soil organisms and microbial mineralization of organic substrates in peatlands (Moore and Dalva 1997;Laiho et al 2001;Makiranta et al 2009;Hribljan et al 2014;Bragazza et al 2016;Schmidt et al 2016), as well as the activities of phenoloxidase and peroxidase (Fenner and Freeman 2011;Peacock et al 2015;Dieleman et al 2016a), hence leading to an increase in hydrolase activity and decomposition rate (Moore and Knowles 1989;Silvola et al 1996;Nykanen et al 1998;Minkkinen et al 1999;Freeman, Ostle, and Kang 2001;Jaatinen et al 2008;Peacock et al 2015;Wu et al 2017). For example, phenolic-degrading bacteria are more diverse and have higher phenoloxidase activity under short-term drought, which further increases CO 2 flux (Fenner, Freeman, and Reynolds 2005).…”
Section: Effects Of Water Level Alteration On Organic Matter Decomposmentioning
confidence: 99%
“…See aerobic and anaerobic decomposition in Figure 1. Drawdown alleviates oxygen limitation and increases soil aeration, which promotes the activities of soil organisms and microbial mineralization of organic substrates in peatlands (Moore and Dalva 1997;Laiho et al 2001;Makiranta et al 2009;Hribljan et al 2014;Bragazza et al 2016;Schmidt et al 2016), as well as the activities of phenoloxidase and peroxidase (Fenner and Freeman 2011;Peacock et al 2015;Dieleman et al 2016a), hence leading to an increase in hydrolase activity and decomposition rate (Moore and Knowles 1989;Silvola et al 1996;Nykanen et al 1998;Minkkinen et al 1999;Freeman, Ostle, and Kang 2001;Jaatinen et al 2008;Peacock et al 2015;Wu et al 2017). For example, phenolic-degrading bacteria are more diverse and have higher phenoloxidase activity under short-term drought, which further increases CO 2 flux (Fenner, Freeman, and Reynolds 2005).…”
Section: Effects Of Water Level Alteration On Organic Matter Decomposmentioning
confidence: 99%
“…The decline in water table through processes, such as drainage, could increase the CO 2 emission fluxes and reduce the CH 4 emission fluxes (Gorham, 1991; Moore & Knowles, 1989; Roulet, 2000; Urbanová et al., 2013), resulting in a net loss of C storage from soil (Heinemeyer & Swindles, 2018; Wu et al., 2017). In this study, the C emission fluxes associated with the wet and dry meadows were 2.51 and 4.94 times more than that in the peatland, respectively (Figure 3c).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, increasing soil pH can also have significant effects on relative abundance of arbuscular mycorrhizal fungi (i.e., Glomus and Acaulospora), which can result in considerable SOC decomposition under elevated CO 2 (Cheng et al, 2012). Additionally, soil pH can also have significant effects on soil fauna (Liu et al, 2007), which can stimulate soil microorganisms and, further, speed up SOC losses (Wu et al, 2017;Zhou et al, 2014).…”
Section: Effects Of Soil Ph On Soc Concentration In the Tibetan Plateau Shrublandsmentioning
confidence: 99%
“…Regarding the Tibetan Plateau, SOC levels were reported in grasslands (Yang et al, 2009;Wu, Wang, & Sun, 2019), wetlands (Ma, Zhang, Tang, & Liu, 2016;Wang, Qian, Cheng, & Lai, 2002) and permafrost regions (Mu et al, 2015), including alpine swamp meadow, meadow, steppe and desert vegetation (Shang et al, 2016), and SOC was significantly different in various ecosystems (Shang et al, 2016). The SOC variation is likely to be shaped by the following factors: aboveground plant biomass, root biomass, soil texture and mineralogy (Doetterl et al, 2015(Doetterl et al, , 2018Feng, Plante, & Six, 2013;Rasmussen et al, 2018;Wu et al, 2017). Piao et al (2009) have indicated that shrublands were identified as being the most uncertain factor that was contributing to China's C stock due to their less extensive investigation.…”
Section: Introductionmentioning
confidence: 99%